2006
DOI: 10.1177/1043659606288375
|View full text |Cite
|
Sign up to set email alerts
|

Values and Beliefs About Obesity and Weight Reduction Among African American and Caucasian Women

Abstract: Designing culturally relevant weight-reduction programs requires understanding of ethnic variations and illness beliefs. Preliminary data on the values and beliefs about obesity and weight reduction were obtained from women of different ethnic/racial backgrounds. Purposive sampling was used to recruit African American (AA) and Caucasian (C) women with a body mass index (BMI)>or= 30 from the general internal medicine clinics of a large tertiary care facility. Four focus groups (2 with AA women and 2 with C wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
72
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 22 publications
10
72
0
1
Order By: Relevance
“…Participants' comments regarding body size are consistent with the findings of other SA studies (4,7) which have suggested that black SA women prefer a larger body size. Similar findings are evident in other cultures such as Samoan populations of the Pacific Islands (31) , the women of Saudi Arabia (32) , women of Caribbean descent living in the UK (33) and African-American women in the USA (34)(35)(36) . The findings of previous studies suggest that many women of African descent view obesity not only as attractive but also as a sign of wealth and affluence (7,12,16,20) .…”
Section: Discussionsupporting
confidence: 82%
“…Participants' comments regarding body size are consistent with the findings of other SA studies (4,7) which have suggested that black SA women prefer a larger body size. Similar findings are evident in other cultures such as Samoan populations of the Pacific Islands (31) , the women of Saudi Arabia (32) , women of Caribbean descent living in the UK (33) and African-American women in the USA (34)(35)(36) . The findings of previous studies suggest that many women of African descent view obesity not only as attractive but also as a sign of wealth and affluence (7,12,16,20) .…”
Section: Discussionsupporting
confidence: 82%
“…Research indicates that obesity is a highly stigmatised problem [10] associated with blame and personal responsibility [11]. A study by Blixen et al [12] also found that the word 'obese' was considered to be 'vulgar' and connotative of unattractiveness. This suggests that doctors may choose to avoid the medical term for fear of upsetting patients with its negative associations.…”
Section: Introductionmentioning
confidence: 99%
“…In focus groups, obese African-American women cited ethnic and cultural norms, influence of close family members, food cravings, as well as lack of time, resources, self-control, and social support [11,14], obese Caucasian women reported depression and lack of commitment to diet [11], and overweight men discussed inadequate motivation and negative perception of dieting [12]. In a national survey of US adults, barriers to weight loss included inadequate energy (65%), will power (56%), time (44%), and social support (38%) for exercise, as well as high cost of healthy food (49%), preference for junk food (48%), and eating out (40%) [13].…”
Section: Discussionmentioning
confidence: 99%
“…We identified categories a priori from studies describing subjective explanations for obesity [7,[10][11][12][13][14], as well as from our clinical experience. We identified additional relevant categories by reviewing three sets of randomly selected responses consisting of 5%, 10%, and 15% of the total sample, respectively.…”
Section: Research Methods and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation